Varhaislapsuudessa koetun motorisen pätevyyden yhteydet alakouluiän motorisiin taitoihin - Meuronen, Joonas; Katila, Tuomas (2024)
The purpose of this longitudinal study was to conduct associations between 5–7-year-olds perceived motor competence and 6–11-year-olds actual motor skills. In addition, gender differences in these associations were studied. Two of the main variables, perceived motor competence (PMC) and motor skills (MS), were examined separately.